Designing a structure of the magnetically active part of dipole electromagnets for the system of vertical convergence-separation of beams - Getman, Andriy (РС Теshnology Сentеr, 2021)
This paper reports the results of calculating the magnetic parameters for a direct dipole magnet in the system of vertical convergence-separation of particle beams of the upper and lower rings of the heavy-ion collider. An optimized variant of the yoke and superconducting winding structures has been obtained, providing for the assigned value of a homogeneous magnetic field inside the aperture at the minimized contributions of higher-order harmonics, average-integral along the length. The results from the analysis of the transverse pro-jections of the magnetic induction obtained by 2D modeling of two variants of the design of the central cross-section of the dipole electromagnet are presented. The analysis results have established the dependence of the stability of magnetic parameters in the aperture of the electromagnet when the current in the winding changes on the volume of those yoke regions whose magnetization value is close to saturation. A 3D model of the magnetically active part has been built for two variants of the electromagnet design, and the values of the average-integral harmonics of transverse projections of magnetic induction in the aperture have been calculated. The relationship between the third average-integral harmonic of magnetic induction and the size lengths of the yoke and winding has been empirically established, making it possible to correct the heterogeneity of the transverse magnetic field in the aperture of the electromagnet. The results of optimization of the structure of the magnetically active part of the electromagnet are presented on the criteria for a minimum of the values of the average-integral coefficients of magnetic induction, carried out on the basis of correction of the initial geometric parameters of the yoke and winding. An improvement in the stability of magnetic parameters has been demonstrated, by 3 times, as well as a two-fold reduction in the con-tribution to the heterogeneity by the third average-integral harmonic when using a two-row arrangement of the winding turns inside the yoke in the design of the electromagnet.
Keywords: dipole electromagnet; superconducting winding; beam of particles; magnetic field harmonic coefficient